Power Balance Optimization Technology of Microgrid Based on Full-Bridge Converter - Shuailong Dai; Bin Cao; Rui Liu; Liyang Zhu; Mengfan Li (Complexity, 2020)
Independent microgrids are widely used in islands and remote townships. However, power imbalance often leads to fluctuations in voltage and frequency, which inhibit the development of AC microgrids. To overcome such problems, this paper proposes an optimized full-bridge converter energy storage structure to realize power balance and optimization of the microgrid. The proposed structure has the characteristics of simple design, easy modularization, and flexible power regulation. First, the working structure and mathematical model are analyzed, and the power model is then established. From the viewpoint of capacitor charging and discharging and inverter, the active and reactive power control technology of the full-bridge structure is analyzed, and a multimode power coordinated control strategy is adopted to adjust and optimize the target power. Finally, the feasibility of the structure and control strategy is verified through a simulation and an experiment. In summary, this study is of great significance to the future promotion and application of AC microgrids.